The Effect of Tiktok Short Videos towards Students’ Vocabulry Mastery: A Quantitative Research Approach - Irawansyah; Ferry Desryananda; Abdul Malik Akbar (PANYONARA: Journal of English Education, 2025)
TikTok, apart from being an entertainment platform, holds a valuable function as a tool to assist students in acquiring new vocabulary. This study aims to examine the effect of educational videos on TikTok on students’ vocabulary mastery. This study employed a quasi-experimental method, involving members of UKM Bahasa at Universitas Islam Negeri Raden Intan Lampung that contained 30 students. To get an appropriate sample, purposive sampling was used. This study used the pre-test and post-test as the instruments to measure students’ vocabulary mastery before and after the treatments. The data were analysed by using validity, reliability, normality, and homogeneity tests. Along with that, there was a significant improvement: the average score on the pre-test was 49.96, and the average score on the post-test was 70.2. Additionally, this study successfully found a significant effect between between the use of TikTok educational videos and studentsâ€™ vocabulary mastery. This highlights TikTok’s potential as a useful learning tool.